2023
DOI: 10.3389/fncel.2023.1130505
|View full text |Cite
|
Sign up to set email alerts
|

The cerebellum and anxiety

Abstract: Although the cerebellum is traditionally known for its role in motor functions, recent evidence points toward the additional involvement of the cerebellum in an array of non-motor functions. One such non-motor function is anxiety behavior: a series of recent studies now implicate the cerebellum in anxiety. Here, we review evidence regarding the possible role of the cerebellum in anxiety—ranging from clinical studies to experimental manipulation of neural activity—that collectively points toward a role for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 125 publications
1
6
0
Order By: Relevance
“…Specifically, the lower nodal degree in the left cerebellum of the structural connectome, the worse behaviors exhibited in dogs with anxiety disorders. This result is consistent with recent studies both in humans and animals that illustrates that the cerebellum plays a crucial role in fear and anxiety-related behaviors 91 , 108 110 . Structural and functional abnormalities in the cerebellum may lead to the expression of exacerbated fear and anxiety-related behaviors toward situations that do not suppose a real threat 89 , 111 .…”
Section: Discussionsupporting
confidence: 93%
“…Specifically, the lower nodal degree in the left cerebellum of the structural connectome, the worse behaviors exhibited in dogs with anxiety disorders. This result is consistent with recent studies both in humans and animals that illustrates that the cerebellum plays a crucial role in fear and anxiety-related behaviors 91 , 108 110 . Structural and functional abnormalities in the cerebellum may lead to the expression of exacerbated fear and anxiety-related behaviors toward situations that do not suppose a real threat 89 , 111 .…”
Section: Discussionsupporting
confidence: 93%
“…IC-GM 7 includes instead regions of the cerebellum, which, despite its typical role in motor functions, has being more and more investigated in different cognitive and emotional processes, leading to an extension and rede nition of its traditional roles towards new ones, ranging from emotion regulation and impulsive decision making inhibition to working memory and attention 43 . Studies performed in both rodents and humans have found the cerebellum to be involved in many psychiatric disorders, such as anxiety disorders, in which it tends to show an hyperactivation 43,44 . Research on fear and anxiety-related disorders connects the cerebellum to processes of aversive stimuli-related prediction, in particular to the use of threatening/anxious memories which lead to the attribution of aversiveness and harmfulness to the new faced situation/stimulus 45 .…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between cerebellar and affective functioning is increasingly appreciated in the clinical literature, indicating cerebellar involvement in disorders such as attention deficit disorder, schizophrenia, bipolar disorder, depression, anxiety disorders and importantly, cerebellar dysfunction is the mechanism underlying the cerebellar cognitive affective syndrome (Baek et al, 2022; Depping et al, 2018; Ke et al, 2016; Liao et al, 2010; Phillips et al, 2015; Schmahmann and Sherman, 1998). Several of these disorders have an anxiety component, although this may be bidirectional and topographically mediated (Chin and Augustine, 2023). In rodent models, lesions of the cerebellar vermis have been found to increase anxiety-like behavior (Bobée et al, 2000; Supple et al, 1987), and other areas have no effect on anxiety behaviors indicating that not all cerebellar cortices influence anxiety behaviors (for review, see (Chin and Augustine, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Several of these disorders have an anxiety component, although this may be bidirectional and topographically mediated (Chin and Augustine, 2023). In rodent models, lesions of the cerebellar vermis have been found to increase anxiety-like behavior (Bobée et al, 2000; Supple et al, 1987), and other areas have no effect on anxiety behaviors indicating that not all cerebellar cortices influence anxiety behaviors (for review, see (Chin and Augustine, 2023). Models of either purkinje cell neurodegeneration (Spinocerebellar ataxia rodent model) or total purkinje cell loss (Lurcher mouse) in the cerebellum have largely been found to exhibit anxiolytic behavior (Boy et al, 2009; Hilber et al, 2004; Lorivel et al, 2010; Monnier and Lalonde, 1995); however, some anxiogenic behaviors have been reported (Kelp et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation